Gut microbiome and prediabetes - a review - Rathi, Kartik Kumar; Kumari, Nimrata; Javaid, Muhammad Daniyal; Saleem, Umair; Mortensen, Eric; Zhou, Yanjiao; Maheshwari, Narinder (Frontiers in Bacteriology, 2023)
While there is extensive information available on how the gut microbiota alters in composition between normal individuals and known diabetics, there is little evidence available on whether the alterations become apparent at the prediabetic stage (a preliminary state to T2DM which is characterized by altered glycemic parameters relative to a normal euglycemic state), and if these variations are potentially linked with the progression from prediabetes into diabetes. In this review, we aim to summarize all the findings on compositional shifts in the gut microbiome that are shown to occur in pre diabetics and diabetics in contrast to euglycemic states. Our review also highlights the potential pathophysiological mechanisms that could explain these alterations in metabolism due to the presence of varying microbial environments in the gut. Moreover, we also gather the available evidence on the role played by various factors, such as dietary changes and exercise, and their potential role in inducing a change in the gut microbiome. Last but not least, our review also assesses changes to the microbiota population brought about by a subsequent probiotic and symbiotic supplementation, Metformin and Acarbose. Additionally, we also evaluate the use of above mentioned interventions in mitigating the progression of prediabetes into subsequent diabetes mellitus. We believe this review can help understand the dynamic role played by the gut microbiome in the onset of prediabetes and if there is a possibility of reverting back to euglycemia with correct measures.